LAMELLAR KERATOPLASTY WITH THE CROSS-LINKING APPLICATION IN TREATMENT OF KERATOCONUS - M.A. MEDVEDEV; B.KH. BEBEZOV; N.A. TURGUNBAEV; A.I. OSTROVERKHOV (Avicenna Tajik State Medical University, 2020)
Objective: To study the effectiveness and safety of using a combination of lamellar keratoplasty and cross-linking in the treatment of keratoconus. Methods: There nine patients (9 eyes) with keratoconus of stage III (Amsler) on the worst eye were under surveillance. The patients before and afterward the surgery were performed visometry, biomicroscopy, and ophthalmometry. In all cases, the operation was performed on the eye with lower visual acuity. The excision of corneal tissue up to the Descemet's membrane was carried out using a zirconium (fianite) exfoliator. The diameter of the graft corresponded to the diameter of the tissue bed. After applying four fixing silk sutures (silk 8.0) have put in the continuous stitches of 10.0 size (nylon, supramide). Before starting the cross-linking procedure, an intrastromal donor transplanted cornea was saturated with an insulin syringe with a 0.1% riboflavin solution. The surgical field was subsequently exposed to UVA irradiation with a wavelength of 370 nm according to the express method. All patients were followed up for a period of 6 months up to 5 years. Results: Total epithelization in all cases is noted for the first 24 hours. Early medicinal therapy in the postoperative period included the appointment of antibiotics and corticosteroids in instillations. A continuous suture in all cases was removed between the 3rd and 4th month after surgery. By the 6th month after the operation, uncorrected visual acuity was 0.39±0.12. The maximum corrected visual acuity was 0.47±0.11. The average level of postkeratoplastic astigmatism was 2.66±0.97D. Conclusion: It can be considered, that the biological results of lamellar keratoplasty exceed those of the through corneal transplant. While the functional results of lamellar keratoplasty with the cross-linking application are slightly lower than those of the through keratoplasty; which explained to the availability of the additional refraction plane (interface).